Is the chemical control of glyphosate-resistant hairy fleabane more efficient during pre-flowering or re-growth? (Revista de Ciências Agroveterinárias, 2016)
To test the efficacy of alternative herbicides for controlling of glyphosate-resistant Conyza bonariensis under different growth stages, we carried out an experiment in an apple orchard, in a factorial arrangement 2x5, consisting of: (i) two growth stages – pre-flowering and re-growth; and (ii) five herbicides – glyphosate, glufosinate, bentazon, diquat, and glyphosate+saflufenacil. Basagran, diquat, and glyphosate+saflufenacil were not efficient to control C. bonariensis in pre-flowering. Glufosinate, diquat, bentazon, and glyphosate+saflufenacil controlled C. bonariensis in re-growth. Just glufosinate showed efficient control (>90%) of C. bonariensis in both pre-flowering and re-growth. In general, control of C. bonariensis is more efficient in re-growth.
Keywords: Conyza bonariensis; herbicides; growth stage.